Systematic position of the enigmatic African cycad moths: an integrative approach to a nearly century old problem (Lepidoptera: Geometridae, Diptychini). (4th March 2015) - SIHVONEN, PASI; STAUDE, HERMANN S.; MUTANEN, MARKO
Abstract The systematic position and hierarchical level of the moth taxon Diptychini Janse (Lepidoptera: Geometridae), the cycad moths, has remained controversial. This is partly due to their unique morphological and biological characteristics. To study the systematics, comprehensive molecular analyses of eight genes, in total 6157 bp, were carried out. We used Bayesian inference to construct phylogenetic trees. The first analysis (46 Geometridae and 7 non‐Geometridae taxa, representing all recently recognised Geometridae subfamilies) demonstrated that the Diptychini belong to the Geometridae subfamily Ennominae. The second analysis, focused on the Ennominae (70 taxa, representing 28 of 30 recently recognised Ennominae tribes worldwide), found that the Diptychini are nested well within the Ennominae; it is monophyletic and associated with the complex of southern Hemisphere Nacophorini, refuting many of the earlier hypotheses about Diptychini relationships. The Diptychini are considered tentatively valid at the tribe level, but relationships with the Nacophorini and the Lithinini need further research. The molecular findings were evaluated from a morphological point of view, which are mostly in agreement with the molecular results. The Diptychini genera are illustrated and characterised using morphological and life‐history traits. Within the Diptychini, three genera are considered valid. Durbana Warren (described in 1904) is proposed as a junior synonym of Veniliodes Warren (described in 1894) (n.syn.). Monotypic Larentioides Prout is combined with the tribe Lithinini (n.comb.). Homonymy of Diptychini Mirza (described in 1991) (Pisces: Cyprinidae, Schizothoracinae) with Diptychini Janse (described in 1933) (Lepidoptera: Geometridae, Ennominae) is noted, the former requiring a replacement name.